The behavioral basis of sell-side analysts’ herding - Durand, Robert; Limkriangkrai, M.; Fung, L. (Elsevier Ltd, 2014)
Sell-side analysts move away from the prevailing consensus as their confidence increases. As their confidence falls, they herd toward the prevailing consensus. Confidence as well as the associated propensity to move away from the herd increase as firms become more difficult to analyze. This behavior is consistent with such analysts having lower meta-cognitive skills.